Uses and Applications of Docosahexaenoic Acid (DHA) in Pediatric Gastroenterology: Current Evidence and New Perspective - Jiménez, David González; García, Carlos Bousoño; Martín, Juan J. D. (Current Pediatric Reviews, 2021)
In this paper, we will review the dietary allowances of these fatty acids in the paediatric population, and also the indications in different pathologies within the field of pediatric gastroenterology. Finally, we will try to explain the reasons that may justify the difficulty in translating good results in experimental studies to the usual clinical practice. This “good results” may be too little to be detected or there may be other causes but misinterpreted as effects of DHA.
Keywords: DHA